Issues of art education in cultural and historical discourse. - Tsuranova, Oksana; Haleeva, Оlena (My University, 2020)
У роботі розглядаються питання музичної освіти у культурному та історичному дискурсі.
Tsuranova O. Issues of art education in cultural and historical discourse / O. Tsuranova, O. Haleeva // Challenges in Science of Nowadays : proceedings of the 3rd International Scientific and Practical Conference. – Washington, USA, 2020. – P. 72–75.
Keywords: музична педагогіка, вокально-хорова освіта, мистецтво; music pedagogy, vocal and choral education, art; музыкальная педагогика, вокально-хоровое образование, искусство